The Clinical Study on the Effect of Hominis Placenta Pharmacopuncture on Asthma - Lee So-yol; Shin Kyung-min; Hong Jang-mu; Choi Soon-young; Bae Kwang-rok; Kim Han-kyum (Korean Pharmacopuncture Institute, 2008)
Objectives : The purpose of this study is to report the effect of Hominis Placenta Pharmacopuncture(HPP) for patients with asthma. Methods : We treated three patients who have asthma with HPP. To check the effect of HPP we used CAMSOMV. To check the satisfaction of HPP we used Five-point Likert scale. Results : After treatment symptoms were improved. CAMSOM-V decreased in all cases. The Likert scale points were checked 5 and 4 and 4. Conclusions : In this study, we have found the meaning of the research that HPP, in the future will be efficacious against asthma.